HUBUNGAN TINGKAT PENGETAHUAN POLA MAKAN DENGAN FAKTOR RESIKO DIABETES MILITUS PADA REMAJA - Nida Lutfiawati (Nusantara Hasana Berdikari, 2021)
Background: Diabetes mellitus (DM) is a progressive chronic disease due to the body's inability to metabolize carbohydrates, proteins and fats, leading to hyperglycemia (high blood glucose levels). both clients and health care providers commonly refer to Diabetes Militus as “high blood sugar”. Many factors can affect diabetes mellitus, including knowledge and diet. Research Objectives: To determine the relationship between the level of knowledge of eating patterns with risk factors for Diabetes Militus in adolescents at SMAN 14 Tangerang district in 2021. Research Methods: This study is a quantitative study with a quantitative research design with a descriptive method. The population of this study was adolescents aged 16-17 years, the sampling technique used purposive sampling with a total sample of 72 respondents. The instrument used is a questionnaire sheet containing several questions. The data analysis technique used univariate analysis. Research results: Based on bivariate analysis using chi-square that p-value 0.000 <0.05, it can be concluded that Ha is accepted and Ho is rejected so that it can be concluded that there is a significant relationship between the level of dietary knowledge and risk factors for diabetes mellitus in adolescents at SMAN 14 Kab. Tangerang. Conclusion: There is a relationship between the level of knowledge of eating patterns with risk factors for Diabetes Militus at SMAN 14 Tangerang district in 2021. Suggestion: It is hoped that it can be useful for readers.